Urgensi Pengaturan Pembuatan Surat Keterangan Waris Terkait Pembagian Golongan Penduduk Di Indonesia - Sugitha, Ketut Nindy Rahayu; Dahana, Cokorda Dalem (Acta Comitas : Jurnal Hukum Kenotariatan, 2021)
Abstract This scientific article purpose is understand the arrangements regarding the issuance of Certificate of Inheritance related to the division of population groups in Indonesia. The method used is normative legal research. This study result is indicate that the arrangement for making a certificate of inheritance related to division of population groups in Indonesia is regulated in Article 111 paragraph (1) of Ministerial Regulation No. 3 of 1997 on the Implementation of Land Registration which divides into 3 (three) groups, namely Indonesian Citizens, Indigenous People, Chinese Descendants. and Foreign Eastern Descent, then there are also 3 (three) officials who have the authority to make a certificate of inheritance in Indonesia according to their class. This classification raises the problem that Ministerial Regulation Number 3 of 1997 on the Implementation of Land Registration is contrary to Law Number 40 of 2008 on Elimination of Discrimination which is a higher regulation and should eliminate the classification of society related to the issuance of a certificate of inheritance in Indonesia. The urgency of a notary to be given the authority to make a deed of inheritance rights because a notary is an official who makes a deed whose legal force of proof is perfect, guaranteed order, certainty, and legal protection. Article 15 paragraph (1) of the Law on Notary Positions becomes the basis for Notaries in acting and constructing a Certificate of Inheritance for all residents and/or citizens of Indonesia, in order to create legal certainty for makers of Certificate of Inheritance in Indonesia. Abstrak Tujuan artikel ilmiah ini yaitu untuk memahami pengaturan mengenai dibuatnya Surat Keterangan Waris terkait pembagian golongan penduduk di Indonesia. Metode yang digunakan adalah penelitian hukum normatif. Hasil penelitian ini menunjukkan bahwa pengaturan dibuatnya surat keterangan waris terkait pembagian golongan penduduk di Indonesia diatur pada Pasal 111 ayat (1) Peraturan Menteri Nomor 3 Tahun 1997  Pelaksanaan Pendaftaran Tanah yang membagi atas 3 (tiga) golongan yaitu golongan Warganegara Indonesia Penduduk Asli, Keturunan Tionghoa dan Keturunan Timur Asing, kemudian terdapat juga 3 (tiga) pejabat yang memiliki wewenang dalam dibuatnya suatu surat keterangan waris di Indonesia sesuai dengan golongannya. Penggolongan semacam ini menimbulkan permasalahan bahwa Peraturan Menteri Nomor 3 Tahun 1997 Pelaksanaan Pendaftaran Tanah sudah bertentangan dengan UU Nomor 40 Tahun 2008 Penghapusan Diskriminasi yang merupakan aturan yang lebih tinggi dan sudah seharusnya menghilangkan penggolongan masyarakat terkait dibuatnya surat keterangan waris di indonesia. Urgensi notaris diberikan kewenangan dalam pembuatan akta keterangan hak waris karena Notaris merupakan pejabat yang membuat akta yang kekuatan hukum pembuktiannya bersifat sempurna, terjamin ketertiban, kepastian, dan perlindungan hukum. Pasal 15 ayat (1) UU Jabatan Notaris menjadi dasar Notaris dalam bertindak dan mengkonstruksi sebuah Surat Keterangan Waris untuk semua penduduk dan/atau warga negara Indonesia, agar menciptakan kepastian hukum bagi pembuat Surat Keterangan Waris di Indonesia.